2017
DOI: 10.2174/1874922401709010160
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Aware Schools: Working with Families to Enhance Parental Engagement and Home-School Relationships

Abstract: Background:Application of attachment theory in school contexts lacks empirical evidence. The Attachment Aware Schools pilot project was commissioned by two Local Authorities in England to improve the educational outcomes of Looked After Children, and to build an evidence base. Informed by attachment research, the Attachment Aware Schools program provides a coherent and integrated theoretical framework, discourse, and practice for all practitioners working with children and young people.Objective:The primary fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Staff also reported improved relationships with parents thus strengthening personal and community 'school bonding' (Bergin and Bergin, 2009). The way in which the project fostered parental engagement and improved relationships between home and school is documented elsewhere (Rose et al, 2017).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Staff also reported improved relationships with parents thus strengthening personal and community 'school bonding' (Bergin and Bergin, 2009). The way in which the project fostered parental engagement and improved relationships between home and school is documented elsewhere (Rose et al, 2017).…”
Section: Discussionmentioning
confidence: 92%
“…The AAS framework (see model below) comprised of key elements to support effective implementation, such as school ethos, specific training packages promoting identifiable strategies, collaborative partnerships with the wider community and building an evidence base of practice. Preliminary pilot research findings have shown positive results (Rose et al, 2015;Rose et al, 2017).…”
Section: Attachment Aware Schools Rationalementioning
confidence: 99%
See 1 more Smart Citation